JOB BURNOUT AND PERFORMANCE OF STAFF NURSES IN SELECTED HOSPITALS IN METRO MANILA - De Leon, Kathleen G; Reyes, Jennifer P; Martinez, Ma. Cecilia O (LIFE: International Journal of Health and Life-Sciences, 2021)
This study was conducted to determine the job burnout and performance of staff nurses in selected tertiary hospitals in Manila using the Oldenburg Burnout Inventory. Results showed that there’s: a high degree of agreement in relation to burnout of the staff-nurses in terms of exhaustion and disengagement; an average level of performance of the staff nurses in terms of task performance, contextual performance, and counter-productive behavior; significant differences between the degrees of agreement in relation to job burnout of the staff-nurses (disengagement and exhaustion) when they are grouped according to nurse-patient ratio and census per area; significant relationships between the degree of agreement in relation to job burnout (disengagement) and overall level of performance of the staff nurses. Researchers pursued this study because some of their colleagues have lost the enjoyment of their job; that they feel that their efforts were being unnoticed; and feel overworked. Through this study, the degree of agreement in relation to job burnout of the staff nurses and their level of performance was determined. This paved a way for the development of new plans and programs to help staff nurses overcome their feelings of burnout, making them more energetic and enthusiastic in performing their job.